Highly transparent electrorheological fluids of silica nanoparticles: the effect of urea modification. Issue 33 (10th August 2016) - Hao, Bo Nan; Guo, Yun Xia; Liu, Ying Dan; Wang, Li-Min; Choi, Hyoung Jin
Abstract : Highly transparent electrorheological (ER) fluids with enhanced ER properties were prepared using urea-modified silica nanoparticles. Abstract : Silica nanoparticles modified with urea molecules were used as a dispersed phase to prepare optically transparent electrorheological (TER) fluids by using a refractive index matching method. The effect of modification by urea was studied by analysing four samples of silica nanoparticles treated by urea solutions with different concentrations. Transparency and electrorheological (ER) performances of the TER fluids were characterised by a visible spectrometer and a rotational rheometer, respectively. Dielectric properties of the TER fluids, as determined by a broadband dielectric spectrometer, were well correlated with their ER characteristics. Our experimental results also showed that the shear stress and storage modulus of the TER fluids were effectively increased by the modification with urea. In addition, with increasing urea concentration, the corresponding TER fluids had a higher dielectric constant, but lower transparency and sedimentation stability.